2014
DOI: 10.3390/ijms150916012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Dermatophyte Species after Implementation of the In-House MALDI-TOF MS Database

Abstract: Despite that matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry (MS) has become a powerful tool in the clinical microbiology setting, few studies have till now focused on MALDI-TOF MS-based identification of dermatophytes. In this study, we analyze dermatophytes strains isolated from clinical samples by MALDI-TOF MS to supplement the reference database available in our laboratory. Twenty four dermatophytes (13 reference strains and 11 field isolated strains), identified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 18 publications
2
45
0
2
Order By: Relevance
“…Prior studies have evaluated the accuracy of MALDI-TOF MS for the identification of only a few genera or groups of organisms, such as Aspergillus spp. or the dermatophytes (12,13,(19)(20)(21)(22)(23)(24)(25)(26). In our study, which examined 319 isolates from 43 different genera, the Vitek MS version 3.0 library was able to correctly identify 66.8% of isolates and 76.8% of the isolates after additional SARAMIS analysis.…”
Section: Discussionmentioning
confidence: 75%
“…Prior studies have evaluated the accuracy of MALDI-TOF MS for the identification of only a few genera or groups of organisms, such as Aspergillus spp. or the dermatophytes (12,13,(19)(20)(21)(22)(23)(24)(25)(26). In our study, which examined 319 isolates from 43 different genera, the Vitek MS version 3.0 library was able to correctly identify 66.8% of isolates and 76.8% of the isolates after additional SARAMIS analysis.…”
Section: Discussionmentioning
confidence: 75%
“…All 64 isolates were correctly identified (score value of Ͼ2.0 for 47 isolates and score value of 1.7 to 2.0 for the remaining 17 isolates) with the implemented database, including the M. audouinii isolate (misidentified as M. canis), 2 T. violaceum isolates (not reliably identified; score value of Ͻ1.7), 1 T. tonsurans isolate (misidentified as T. rubrum), 3 T. rubrum isolates (2 misidentified as T. tonsurans and 1 not reliably identified), 2 T. soudanense isolates (1 misidentified as T. rubrum and 1 not reliably identified), and 1 M. persicolor isolate (not reliably identified). As expected, with regard to T. mentagrophytes-T. interdigitale isolates (19 and 2, respectively; not distinguished by their ITS sequences), all but 2 isolates were misidentified as T. tonsurans: 1 of the 2 isolates was misidentified as M. gypseum, and the other one was not reliably identified (32). A more recent evaluation of the performance of the Bruker Biotyper system showed that MALDI-TOF MS provided correct genus-level and species-level identifications for 96.8% (122/126) and 87.9% (113/126) of dermatophyte isolates, respectively, using a supplemented database (the MALDI Biotyper Support Library, i.e., created by adding spectra from 10 reference dermatophyte strains) and decreased score values (33).…”
Section: Rhizopus-lichtheimia Species Previous Reports On the Maldi-mentioning
confidence: 80%
“…It is worth noting that A. flavus, the second leading cause of human aspergillosis, is not separable from Aspergillus oryzae by means of molecular biology techniques, whereas the closely related species T. mentagrophytes and T. interdigitale are not separable by means of ITS sequence analysis. In contrast, MALDI-TOF MS seems to be more powerful for discrimination between these species (10,32) as well as to distinguish clinically relevant from irrelevant species of Lichtheimia (26). However, as MALDI-TOF MS-based identification should be consistent with the aspect of the organism in culture, relatively mature growth must be achieved before the identification is certain.…”
Section: Mold Identification By Maldi-tof Ms: Is It Really a History mentioning
confidence: 99%
See 2 more Smart Citations